PREVALENSI INFEKSI SOIL TRANSMITTED HELMINTH PADA MURID SEKOLAH DASAR NEGERI 105296 KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG, SUMATERA UTARA - Muhammad Jabbar Rahman Tapiheru; Nurfadly Zain (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Soil Transmitted Helminths infection is the most common worm infection found in humans. The prevalence of STH infections in Indonesia is generally still high, mostly in populations with poor sanitation, with varying data of 2.5% - 62% and the highest intensity obtained among preschoolers and primary schools. Objective: This study aims to determine the prevalence of STH infections in public elementary school students 105296 in Percut Sei Tuan sub-district, Deli Serdang District, North Sumatra. Method: This type of research uses descriptive analytic research methods with cross sectional approach. Results: The prevalence of STH infections in grade I-VI students of SD Negeri 105296 Percut Sei Tuan in 2019 is 29.9%. The types of worms that infect are Ascaris lumbricoides worms at 23.1%, Trichuris trrichiura with a percentage of 65.4%, Hookworm not found and mixed infections 11.5% of all samples. Conclusion: The prevalence of STH infections in grade I-VI students of SD Negeri 105296 Percut Sei Tuan in 2019 is 29.9%. The infection is rather high, which should have been greatly reduced or even no more STH infections.